Pengaruh PAD dan Dana Perimbangan terhadap Belanja Modal dengan Pertumbuhan Ekonomi sebagai Variabel Moderasi pada Provinsi di Indonesia - Rendy Alvaro; Adhi Prasetyo Satrio Wibowo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2020)
This study uses EViews 9 to analyze panel data consisting of cross-sections and time series in 33 provinces from 2010-2018. From the test results, it is found that PAD, DAK, and DBH have a significant positive effect on capital expenditure. The DAU does not affect capital spending, while economic growth has a significant negative effect on capital spending. Furthermore, economic growth moderates PAD and DAU has a significant positive effect on capital spending, but economic growth moderated DAK and DBH had a significant negative effect on capital spending.